Sexual Hallucinations in Schizophrenia Spectrum Disorders and Their Relation With Childhood Trauma - Blom, Jan Dirk; Mangoenkarso, Esmeralda (Frontiers in Psychiatry, 2018)
Background: Sexual hallucinations are probably the most neglected types of hallucination, even in psychiatric settings. They are often multimodal in nature, and their prevalence rate is unknown. For other types of hallucination, notably auditory hallucinations, childhood trauma is an important risk factor. However, whether this also applies to sexual hallucinations is unknown. Objective: To establish the prevalence rate of sexual hallucinations in a clinical sample of patients diagnosed with a schizophrenia spectrum disorder, to describe their phenomenological characteristics, and to estimate their relationship with childhood trauma. Methods: After screening 778 patients diagnosed with a schizophrenia spectrum disorder, 42 were considered eligible for inclusion by their treating physician or psychiatrist. Thirty of these patients were interviewed to assess the presence of sexual hallucinations, using a tailor-made questionnaire and the short form of the Childhood Trauma Questionnaire. Results: Of the 30 patients interviewed, 13 reported sexual hallucinations, yielding a one-year prevalence rate of 0.017 in this clinical sample. Of the hallucinating patients, 46.2% reported multimodal hallucinations, with involvement of up to five sensory modalities. All patients who experienced sexual hallucinations reported a history of childhood trauma, of which 76.9% involved sexual trauma (OR 8.7). In addition, 61.5% of the patients reported high levels of distress. Conclusion: In patients diagnosed with a schizophrenia spectrum disorder, sexual hallucinations warrant appropriate medical attention. They are not as rare as traditionally thought, and their relationship with childhood trauma is overwhelming. Therefore, we recommend that clinical attention be paid to the psychotic and traumatic symptoms of these patients, as well as to the somatic conditions that may underlie them. For clinical and research purposes, we propose a classification of sexual hallucinations in accordance with the sensory modalities involved. As sexual hallucinations are also experienced in the context of temporal lobe epilepsy, narcolepsy, persistent genital arousal disorder, intoxications and other somatic conditions, further research in transdiagnostic populations seems warranted. In line with the current practice of providing trauma-focused treatment for trauma-related auditory hallucinations, we recommend that future studies explore the effectiveness of this type of treatment for sexual hallucinations.